The making of economic policy in Africa - Gulhati, Ravi.; Economic Development Institute of The World Bank. (Washington, D.C. : World Bank, 1990)
In January 1989 the Economic Development Institute of the World Bank published case studies that were carried out by the author and two other researchers, and the following year a third on Mauritius. All three discuss policy change in response to internal development and external events affecting these countries. This book summarizes earlier work and extends the analysis, as explained in Chapter one.
Includes bibliographical references: p. 101-111
hza 25/06/2018
Loans
Keywords: Economic policy; Africa, Sub-Saharan